Book review - Uprooting poverty: The South African Challenge (Report for the Second Carnegie Inquiry into Poverty and Development in Southern Africa) (1989) : by Francis Wilson & Mamphela Ramphele - Bentley, Alastair (PINS-Psychology in Society, 2025)
One of the consequences, albeit unintended, of the publication of the First Carnegie Enquiry into the effects of poverty in the early 1930s, was to generate a political response from the government of the day to alleviate the dire poverty of poor whites in South Africa. Using labour legislation as the thrust of their activities they focussed on entrenching white privilege at the expense of black labour. The consequences of this process are highlighted in Wilson & Ramphele's account of the migrant labour system and its catastrophic effects on the social structures and family life of millions of black South Africans. It is the economic forces entrenched in racial capital that serve as the underlying focus of much of the Second Carnegie Report.